2021
DOI: 10.31254/phyto.2021.10211
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Correlation and Path Coefficient Analysis for Yield Attributing and Quality Traits in promising rice varieties cultivated in Tamil Nadu

Abstract: In this study 55 promising rice varieties cultivated in Tamil Nadu was selected and raised in Randomized Block design with two replications. To reveal the nature and degree of correlation and path analysis between yield and quality traits. The results of correlation analysis showed traits like number of filled grains per panicle, productive tillers per plant had positive significant association with the single plant yield. The direct and indirect effects through path coefficient analysis unveils maximum positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…It expressed positive indirect contribution through days to 50% flowering (0.1197) plant height (0.0868), panicle length (0.0766), number of grains per panicle (0.1397), L/B ratio (0.1584), hulling percentage (0.0399) and milling percentage (0.1011) and negative indirect contribution through number of productive tillers per plant (-0.0426), 1000 grain weight (-0.1414), kernel length (-0.0143) and kernel breadth (-0.1754). These results are in agreement with the findings of Premkumar et al [29], Devi et al [3], Hemalatha et al [33] and Naik et al [31].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It expressed positive indirect contribution through days to 50% flowering (0.1197) plant height (0.0868), panicle length (0.0766), number of grains per panicle (0.1397), L/B ratio (0.1584), hulling percentage (0.0399) and milling percentage (0.1011) and negative indirect contribution through number of productive tillers per plant (-0.0426), 1000 grain weight (-0.1414), kernel length (-0.0143) and kernel breadth (-0.1754). These results are in agreement with the findings of Premkumar et al [29], Devi et al [3], Hemalatha et al [33] and Naik et al [31].…”
Section: Resultssupporting
confidence: 93%
“…Head rice recovery exhibited positive and significant correlation with grain yield per plant (0.2107*). These results are in accordance with the findings of Kumar et al [28], Abdala et al [17], Premkumar et al [29], Ratna et al [8], Edukondalu et al [30] Devi et al [3] and Naik et al [31].…”
Section: Resultssupporting
confidence: 92%
“…Hence, these characters could be considered as criteria for higher yield as these were mutually and directly associated with seed yield. Almost similar findings have been reported by [4][5][6][7][8][9][10].…”
Section: Correlations Coefficientssupporting
confidence: 90%
“…Whereas, seed yield plant -1 exhibited negative correlation with days to 50% flowering, plant height, panicle length and days to maturity both at phenotypic and genotypic level (Figure 1). Saleh et al (2020) and Naik et al (2021) observed that the seed yield plant -1 exhibited highly significant and positive correlation with thousand seed weight and numbers of productive tillers plant -1 .…”
Section: Shaded Correlation Matrixmentioning
confidence: 98%